Islamic Personal Development Activities in shaping the Character of Students in Junior High Schools - Wemri Saputra; Ikhwan Rahman; Zulmuqim Zulmuqim; Muhammad Zalnur; Neni Triana; Mutathahirin Mutathahirin (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2023)
This research is to produce graduates who are willing and able to carry out the commands of Allah and His Messenger, stay away from all the prohibitions of Allah and His Messenger, love their nation, and have adequate life skills according to their time. This research is field research using descriptive methods. Results The research is as follows: i) forms of developing students' Islamic character, namely, coaching by example, instilling disciplinary values, coaching by habituation, environmental conditioning, and integration-internalization. ii) forms of Worship Habits, namely, Tahfizh Quran, Dhuha Prayer, Reading Prayers Together, Carrying out Zuhr and Asr Prayers in Congregation and getting used to the Morning and Evening Recitation of Al-Ma'tsurat. iii) the form of Mahabbatul Quran, namely, Recitations of the Quran, Understanding the Quran and Tadabbur Quran iv) the form of Community Service, namely by getting to know the community more closely, improving the quality of relationships with the community and practicing critical thinking. in interacting and communicating with others. v) supporting factors consist of parental support, teachers who have been trained, all teachers are coaches and school culture. Meanwhile, the inhibiting factors are the personality characteristics of students, limited time because there are 2 curricula implemented, namely the National Curriculum and the Curriculum.